Medidas de tendência central e dispersão: uma abordagem com alunos da 3ª série do ensino médio - Siqueira, Jemima Rodrigues de (2021)
This research aims to investigate the implications of a teaching sequence that places the student as the protagonist of the teaching and learning process involving the study of Central Tendency and Dispersion Measures. This experimentation was mainly based on the ideas of Paulo Freire, Vygotski and Iddo Gal, respectively. The qualitative research involved the participation of 35 students of the 3rd grade of High School in the evening period of a public school in the state, located in the city of Araçariguama / SP. The students were responsible for collecting the information, conducting a data survey among the students of the class, based on themes related to their daily lives, which were susceptible to tabulation. From the analysis it was possible to verify that the accomplishment of a sequence of differentiated activities, participative and contextualized with the reality of the students values the involvement and the autonomy of the students. It was also possible to avoid using ready-made formulas, in the teaching and learning process involving the study of Central Tendency Measures and Dispersion Measures, a factor that contributed to the construction of knowledge.